2005
DOI: 10.1142/s1005386705000088
|View full text |Cite
|
Sign up to set email alerts
|

On Endomorphisms of Semilattices of Groups

Abstract: The set of all endomorphisms of an algebraic structure with composition of functions as operation is a rich source of semigroups, which has only rarely been dipped into (see [2]). Here we make a start by considering endomorphisms of Clifford semigroups, relating them to the homomorphisms and endomorphisms of the underlying groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…We start with three propositions which include some already known results. In [10], it is shown that any f ∈ End(S) is determined by f ν . Proposition 1.…”
Section: Regular Endomorphism Monoidmentioning
confidence: 99%
See 4 more Smart Citations
“…We start with three propositions which include some already known results. In [10], it is shown that any f ∈ End(S) is determined by f ν . Proposition 1.…”
Section: Regular Endomorphism Monoidmentioning
confidence: 99%
“…Proposition 1. [10] Let Y be a semilattice which has a least element ν = Y and let S = ξ∈Y G ξ be a Clifford semigroup with injective structure homomorphisms…”
Section: Regular Endomorphism Monoidmentioning
confidence: 99%
See 3 more Smart Citations